Threat Analysis of the Rejection of the Policy on the Excise Extensification of Sugar-Sweetened Beverages in Packaging - Utama, Ramadaan Galih; Subanidja, Steph (Security Intelligence Terrorism Journal (SITJ), 2025)
The excise policy on sugar-sweetened beverages (SSB), which has been regulated in Law No. 7 of 2021 concerning the Harmonization of Tax Regulations, faces significant implementation challenges, especially from the resistance of industry players. The purpose of this study is to analyze the potential threat of rejection of the excise policy on sugar-sweetened beverages (SSB) and formulate an intelligence strategy in dealing with these threats. The research was conducted using qualitative research methods with data collection techniques from in-depth interviews with relevant stakeholders, observations, and library research. The results of the study show that there is a serious threat of policy rejection, which is characterized by a systematic pattern of resistance from industry players through the construction of negative narratives, the utilization of financial capacity for policy interventions, and the momentum of post-pandemic economic vulnerability. Multinational companies with strong financial capabilities and extensive networks have the potential to intervene in the policy process through various strategic approaches. The research recommends the preparation of an integrated intelligence strategy through three dimensions: accelerating the issuance of Government Regulations, building an inclusive multistakeholder dialogue platform, and designing an accommodative transition mechanism. This strategy is formulated to prevent strategic surprises through scenario planning that formulates anticipatory and preventive measures for the implementation of the excise policy on sugar-sweetened beverages (SSB).